Community Development Model in Increasing Productivity Food Security in Rural Areas Based on Local Wisdom - Sulaiman, Adhi Iman; Sugito, Toto; Adi, Tri Nugroho; Murti Susanto, Niken Hapsari Ari; Rofik, Ahmad; Jati, Petrus Imam Prawaoto (Technium Sustainability, 2026)
An in-depth study is needed to provide the best solution for food security productivity, especially in rural areas, based on local wisdom, with a participatory development approach, where all business groups and agricultural resources are involved and collaborate, including with the government, to determine or achieve shared hopes and goals. The purpose of this study is to design a model ccommunity development in increasing food security productivity in rural areas based on local wisdom.The study usedliterature study methodThe results of the study show that the institutions of agricultural cooperatives, farming business groups and fish farms require...Empowerment programs include training and mentoring to improve human resource skills and institutional management. Extension programs are necessary for all business and farmer groups to become members of cooperatives, thereby further strengthening institutions and capital, and promoting shared prosperity. Cooperatives, as the parent institution for joint ventures, can more easily open access to other institutions, such as banks and companies, in order to obtain capital and assistance, such as from Corporate Social Responsibility (CSR). Therefore, business groups such as cooperatives, farmer and fish farmer groups, and small business groups can become community development models that can synergize in increasing productivity and food security in rural areas based on local wisdom